Bifunctional Phosphine Ligand-Enabled Gold-Catalyzed Isomerizations of Alkynamides: Rapid Access to Electron-Rich 2-Aminofurans and Their Diels-Alder Reactions - Li, Xingguang (Angew Chem Int Ed Engl, 2019)
By using biphenyl-2-ylphosphines functionalized with a remote tertiary amino group as ligand, readily available acetylenic amides are directly converted into 2-aminofurans devoid of any electron-withdrawing and hence deactivating/stabilizing substituents. These highly electron-rich furans have rarely been prepared, let alone being applied in synthesis, due to the high reactivities and low stabilities associated with their exceedingly electron-rich nature of the furan ring. In this work, these reactive furans undergo smoothly in-situ intermolecular Diels-Alder reactions to deliver highly functionalized/substituted aniline products or intramolecular ones to furnish carbazole-4-carboxylates in mostly good to excellent yields. This work offers a general and expedient access to this class of rarely studies electron-rich furans and shall open exciting opportunities for their applications.